Agreements on Administration of Titles to Knowhow - Dmytrenko, V.V. (Science and Innovation, 2024)
Introduction. Knowhow is confidential information in the field of intellectual property, which, in particular, implies the specific features of administering intellectual property rights for this object. The theory assumes that there is one legal mechanism to administer intellectual property rights to knowhow that is knowhow transfer agreement, but, at the same time, the transfer of the title to knowhow is understood as granting the right to use it. As a result, practically it is difficult to understand what agreement is to be used to alienate the right to knowhow and to grant the right to use it. Problem Statement. The applicable national intellectual property legislation has not been harmonized. The terms and definitions used in the general and the special legislation for contractual mechanisms of administering intellectual property rights are different, which causes their dual understanding and misunderstanding of the main purpose of agreements on administration of intellectual property rights, which is the administration of the very property rights, not by the objects of intellectual property rights. Accordingly, the choice of contractual mechanism for administering the rights to knowhow is problematic, taking into account the specific nature of the subject of the research associated with its confidentiality. Purpose. To identify possible contractual mechanisms for administering property rights to knowhow. Materials and Methods. The methodological framework of the research is based on the following methods of scholarly knowledge: the general philosophical (in particular, dialectical), the general scholarly (namely, formal logical, structural, comparative and others), and on the special methods of scholarly knowledge used in legal science (for example, comparative, formal and legal, special, etc.). Results. A comparative legal analysis of civil law contracts, including agreements on the administration of intellectual property rights in terms of the possibility of their use in order to grant for use and to alienate title to knowhow has been done. Conclusions. The administration of intellectual property rights to knowhow can be done using all existing contractual mechanisms specified for objects of intellectual property rights in the Civil Code of Ukraine. However, since the freedom of agreement is one of the fundamental principles of the civil law, the separate introduction of knowhow transfer agreement may exist, but in the subject of this agreement it is necessary to clearly identify which exactly rights are granted under this agreement either the right of use or the right of alienation. When concluding agreements on the administration of property rights to knowhow, it is necessary to take into consideration the confidential nature of knowhow.